Androgen receptor activation promotes tumor progression in canine and human triple negative breast cancer cell lines - Caceres, Sara; Crespo, Belen; Herrera, María; de la Puente, Miriam; Diaz Del Arco, Cristina; Alonso-Diez, Angela; Illera, Maria Jose; Illera, Juan Carlos (Frontiers in Veterinary Science, 2025)
IntroductionTriple negative breast cancer (TNBC) is an aggressive type of breast cancer that lack of expression of hormonal receptors and HER-2 that limits the approach of effective therapies. Currently, the expression of the androgen receptor (AR), and its prognostic potential are being explored in these tumors. Therefore, this study aimed to determine the mechanisms of action of AR in TNBC and the potential of AR antagonists as treatment in canine (IPC-366) and human (SUM149) TNBC cell lines.MethodsTo achieve this, AR silencing assays were performed to determine evaluate the changes in AR signaling and the role of AR in cellular processes. Also, the effect of different AR-antagonists was evaluated on both cell lines.ResultsThe findings showed that AR promotes tumor progression by upregulating EGFR expression, which drives cell proliferation through the MAPK and PI3K signaling pathways. Additionally, AR downregulated Src expression, preventing the antiproliferative effects of ERβ, thus ensuring cancer cell survival. The study found that AR activation in TNBC is largely dependent on hormonal signals, highlighting the importance of the balance between androgen and estrogen levels.DiscussionFinally, results revealed that ailanthone acted as a potent AR antagonist, effectively blocking AR and Src expression in both canine and human cell lines, reducing significantly cell proliferation. The study concludes that AR and the tumor’s hormonal environment are critical for TNBC progression and that ailanthone could be a beneficial treatment for both human and canine TNBC.